2023
DOI: 10.1002/slct.202203186
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐based Composite Materials as Catalyst for Organic Transformations

Abstract: Graphene is one of the most auspicious constituents in nanotechnology. It provides the most accurate theoretical 2‐D depiction of catalytic sustenance. Its exceptional, physico‐chemical, and mechanical qualities make it distinctive and also able to create composite materials with novel capabilities. Although using graphene as a single‐layered sheet as a catalytic tool has not been documented yet, certain encouraging outcomes using few‐layer graphene have previously been attained. We will quickly go through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 321 publications
0
1
0
Order By: Relevance
“…26 In this context, GO has been employed as a heterogeneous catalyst in organic reactions such as the ring-opening of epoxides, oxidation reactions of thiols, aza-Michael addition reaction, and Friedel–Crafts addition of indoles to α,β-unsaturated ketones. 27 The synthesis of biaryl compounds via activation of the C–H bond of aryl halides using inexpensive and environmentally friendly GO as a catalyst was demonstrated by Gao et al 28 Basu and coworkers reported the conversion of an aryl amine to unsymmetrical thioether using a “GO bed” under continuous-flow conditions. 29 Nasseri and co-workers synthesized diindolyl-oxindole using GO as an efficient and reusable heterogenous catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…26 In this context, GO has been employed as a heterogeneous catalyst in organic reactions such as the ring-opening of epoxides, oxidation reactions of thiols, aza-Michael addition reaction, and Friedel–Crafts addition of indoles to α,β-unsaturated ketones. 27 The synthesis of biaryl compounds via activation of the C–H bond of aryl halides using inexpensive and environmentally friendly GO as a catalyst was demonstrated by Gao et al 28 Basu and coworkers reported the conversion of an aryl amine to unsymmetrical thioether using a “GO bed” under continuous-flow conditions. 29 Nasseri and co-workers synthesized diindolyl-oxindole using GO as an efficient and reusable heterogenous catalyst.…”
Section: Introductionmentioning
confidence: 99%